Rigid endoscope-assisted orotracheal intubation for vallecular cyst surgery in neonates and young infants. (July 2018) - Tan, Haoyue; Huang, Qi; Paul, Antoine; Wang, Wei; Li, Jingjie; Jia, Huan
Abstract: Objectives: To investigate the outcomes of rigid endoscope-assisted orotracheal intubation (REI) in neonates and young infants with difficult airway conditions as an alternative intubation technique when more specific airway instruments are not available in most developing countries, and to evaluate the safety and advantages of this method. Methods: Neonatal and young infantile patients undergoing vallecular cyst surgery with a Cormack-Lehane Grade 3 or 4 glottic view between June 2013 and June 2015 were studied. Fifteen patients were intubated using rigid endoscopic assistance. Fifteen other patients who were intubated using the conventional technique were selected from the previous consecutive cases and used as a matched control group. Results: REI was successfully performed in all 15 patients in one intubation attempt. The anesthetic preparation duration for the REI group was 6 min (interquartile range 5–7 min), which was shorter than the anesthetic preparation duration for patients intubated using the conventional technique (15 min [interquartile range 10–20 min], p < 0.001). The time required for intubation with a rigid endoscope was 66.5 s (interquartile range 58–74 s). No volume reduction of cysts or tracheotomies was needed in the REI group, and no cysts were ruptured nor did laryngeal mucosa damage occur with this technique. Among patients of conventional group, one required a tracheotomy, and four required cyst volume reduction by needle aspiration. No residual lesions or recurrence were observed during one year of postoperative follow-up in the REI group, and two recurrences were observed in the conventional group. Conclusion: REI, which used common pieces of equipment in an otolaryngology operating room, may be a safe and feasible alternative for intubation in neonatal and young infantile patients with vallecular cysts or other difficult airway conditions.